2013
DOI: 10.1111/dom.12174
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dipeptidyl peptidase-4 inhibitors and metformin as initial combination therapy and as monotherapy in patients with type 2 diabetes mellitus: a meta-analysis

Abstract: Aims: This meta-analysis was performed to provide an update on the efficacy and safety of dipeptidyl peptidase-4 (DPP-4) inhibitors and metformin as initial combination therapy and as monotherapy in patients with type 2 diabetes mellitus (T2DM). Methods:We conducted a search on MEDLINE, Embase and Cochrane Collaborative database for randomized controlled trials (RCTs) of DPP-4 inhibitors and metformin as initial combination therapy or as monotherapy in patients with T2DM by the end of December 2012, using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 47 publications
7
95
0
4
Order By: Relevance
“…The incidence of pancreatic cancer was not assessable due to the short follow-up. In a recent meta-analysis it was demonstrated that DPP-4 inhibitors and metformin combination therapy has a better efficacy than metformin monotherapy, without an increase in any adverse effect, 17,18 confirming the good safety profile of these drugs. In keeping with this, in our study there was no suspension of therapy and the adverse events appeared minor and temporary.…”
Section: Discussionmentioning
confidence: 93%
“…The incidence of pancreatic cancer was not assessable due to the short follow-up. In a recent meta-analysis it was demonstrated that DPP-4 inhibitors and metformin combination therapy has a better efficacy than metformin monotherapy, without an increase in any adverse effect, 17,18 confirming the good safety profile of these drugs. In keeping with this, in our study there was no suspension of therapy and the adverse events appeared minor and temporary.…”
Section: Discussionmentioning
confidence: 93%
“…The results of the first CV trials with DPP-4 inhibitors (3-5) did not meet the expectations of many clinicians, who hoped for a demonstration of a CV benefit, as suggested by meta-analyses of previous, shorter-term studies (8)(9)(10)43). However, CV trials provided exactly the result that they had been designed for: noninferiority versus placebo.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, it was shown that the combination of metformin and a DPP-4 inhibitor is more beneficial than either alone for optimizing glycemic control in type 2 diabetes (24). Metformin augments GLP-1 concentrations by uncertain means (25,26) and in mice, can increase expression of GLP-1 and GIP receptors in pancreatic islets (25).…”
mentioning
confidence: 99%